Predictive factors for sleep apnoea in patients on opioids for chronic pain. Issue 1 (23rd December 2019) - Chung, Frances; Wong, Jean; Bellingham, Geoff; Lebovic, Gerald; Singh, Mandeep; Waseem, Rida; Peng, Philip; George, Charles F P; Furlan, Andrea; Bhatia, Anuj; Clarke, Hance; Juurlink, David N; et al.
Abstract : Background: The risk of death is elevated in patients taking opioids for chronic non-cancer pain. Respiratory depression is the main cause of death due to opioids and sleep apnoea is an important associated risk factor. Methods: In chronic pain clinics, we assessed the STOP-Bang questionnaire (a screening tool for sleep apnoea; S noring, T iredness, O bserved apnoea, high blood P ressure, B ody mass index, age, neck circumference and male gender), Epworth Sleepiness Scale, thyromental distance, Mallampati classification, daytime oxyhaemoglobin saturation (SpO2 ) and calculated daily morphine milligram equivalent (MME) approximations for each participant, and performed an inlaboratory polysomnogram. The primary objective was to determine the predictive factors for sleep apnoea in patients on chronic opioid therapy using multivariable logistic regression models. Results: Of 332 consented participants, 204 underwent polysomnography, and 120 (58.8%) had sleep apnoea (AHI ≥5) (72% obstructive, 20% central and 8% indeterminate sleep apnoea), with a high prevalence of moderate (23.3%) and severe (30.8%) sleep apnoea. The STOP-Bang questionnaire and SpO2 are predictive factors for sleep apnoea (AHI ≥15) in patients on opioids for chronic pain. For each one-unit increase in the STOP-Bang score, the odds of moderate-to-severe sleep apnoea (AHI ≥15) increased by 70%, and for each 1% SpO2 decrease the odds increased by 33%. For each 10 mg MME increase, the odds of Central Apnoea Index ≥5 increased by 3%, and for each 1% SpO2 decrease the odds increased by 45%. Conclusion: In patients on opioids for chronic pain, the STOP-Bang questionnaire and daytime SpO2 are predictive factors for sleep apnoea, and MME and daytime SpO2 are predictive factors for Central Apnoea Index ≥5. Trial registration number: NCT02513836